Selected issues of using international standards of auditing when assessing the application of the going concern basis by management personnel of a company - S. V. Selishchev (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article deals with selected issues of the application of international standards of audit in domestic practice. The source of the main problem, which hinders the development of a unified methodological approach to the application of international standards, is determined, and proposals for its solution are provided. Particular attention is paid to the methodological recommendations for reflecting the requirements of international standards in the auditor’s working papers.The investment activity of foreign partners in Ukraine is conditional on the financial statement clarity for domestic business entities and their trust in them. While the former can achieved by the application of International Financial Reporting Standards, the latter is dependent on the application of International Standards of Auditing (ISA).The purpose of the article is to develop a methodological approach to the application of ISA, based on clarification of their essence and nature.The study of audit practice and opinions of users of audit reports shows that one of the key issues is compliance with the going concern basis of accounting by management personnel in preparing financial statements.It can be concluded from the study that ISA do not conform to the definition of “standards”, being more similar with some kind of “rules”. It means that ISA constitute the rules for performing audit by focusing the auditor attention on a specific set of issues and objects. This approach allows for a certain extent of control over the completeness the audit process and for assuring selected aspects of quality.